A facile synthesis of N-carbamoylmethyl-alpha-aminobutyrolactones by the Ugi multicomponent condensation reaction - Park, SJ; Keum, G; Kang, SB; Koh, HY; Kim, Y; Lee, DH (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
A new method of various N-carbamoylmethyl-alpha-amino-butyrolactones 4 utilizing the intramolecular Ugi five-center-three-component condensation reaction starting from L-homoserine was developed. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: 4-COMPONENT CONDENSATION; COMBINATORIAL TECHNOLOGIES; CONVERTIBLE ISOCYANIDE; DRUG DISCOVERY; SOLID SUPPORT; LIBRARIES; STRATEGIES; PYRROLES; PHASE